Corporate Social Responsibility and Discretionary Social Initiatives in Sport: A Position Paper. Issue 1 (2nd April 2016) - Chelladurai, Packianathan
ABSTRACT: The growing efforts in the study of corporate social responsibility (CSR) in sport are based on the notion that CSR represents the efforts of corporations to do something 'good' to society or some elements of society. In the process, sport management scholars have disregarded an alternate perspective on CSR espoused by economics Nobel Laureate Milton Freedman who said the CSR of a business is its 'business'. This position paper expounds on Milton's doctrine as an emphasis on goal attainment as a social responsibility, and extends the view to include not harming others and rectifying the mistakes that may harm others in the process of attaining the goals as two more social responsibilities of all profit and nonprofit organisations. These social responsibilities are contrasted with the social initiatives an organisation may undertake to benefit society. These social initiatives may or may not be related to the core business of the organisation.